Probable linezolid-induced pancytopenia - Lakhani, Nita (Pulsus Group Inc, 2005)
A 75-year-old male outpatient with cardiac disease, diabetes, chronic renal insufficiency and iron deficiency anemia was prescribed linezolid 600 mg twice daily for a methicillin-resistant Staphylococcus aureus diabetic foot osteomyelitis. After one week, his blood counts were consistent with baseline values. The patient failed to return for subsequent blood work. On day 26, he was admitted to hospital with acute renal failure secondary to dehydration, and was found to be pancytopenic (erythrocytes 2.5x10(12)/L, leukocytes 2.9x10(9)/L, platelets 59x10(9)/L, hemoglobin 71 g/L). The patient was transfused, and linezolid was discontinued. His blood counts improved over the week and remained at baseline two months later. The patient's decline in blood counts from baseline levels met previously established criteria for clinical significance. Application of the Naranjo scale indicated a probable relationship between pancytopenia and linezolid. Clinicians should be aware of this rare effect with linezolid, and prospectively identify patients at risk and emphasize weekly hematological monitoring.